Optimalisasi Penjadwalan Produksi Menggunakan Metode CPM (Critical Path Method) dan Resource Leveling di PT XYZ - Rifqi Azwar Annas; Ade Ima Afifa Himayati; Nunung Agus Firmansyah (CV. ALIM'SPUBLISHING, 2026)
The imbalance in operator allocation and the potential for production delays in the PM11 Emboss Machine manufacturing process at PT XYZ indicate the need for a systematic and efficient scheduling approach. Ineffective scheduling may result in workload fluctuations, uneven resource utilization, and reduced operational performance. This study aims to identify the critical production path using the Critical Path Method (CPM) and balance operator allocation through Resource Leveling. The research used production planning data consisting of 126 operations grouped into six activities. CPM analysis was conducted using POM-QM for Windows to determine the critical path and project duration, while Resource Leveling was performed using Microsoft Project to optimize operator allocation. The results showed that the optimal project duration was 139.66 hours, with the critical path consisting of Frame 1+2+Support Frame and Assy MS Emboss activities. After implementing Resource Leveling, the maximum operator requirement decreased from 17 to 10 operators, the Coefficient of Variation (CV) decreased from 58.35% to 39.10%, and the Standard Deviation decreased from 4.96 to 2.67 without extending project duration. These findings demonstrate that the integration of CPM and Resource Leveling improves scheduling efficiency and supports balanced workload distribution in the PM11 Emboss Machine production process at PT XYZ.